Design of a Problem Based Ubiquitous Learning Model to Improve Thinking Abilities Student Critical - Mislinawati; T. Zulfikar; M. Duskri (Postgraduate, University of Mataram, 2025)
Education plays a crucial role in honing students' critical thinking skills. To achieve this goal, a study developed and tested the validity of the Problem-Based Ubiquitous Learning (PBU-L) model. This model combines Problem-Based Learning (PBL) and Ubiquitous Learning (U-Learning), enabling students to learn collaboratively anywhere and anytime. This study employed a research and development (R&D) method with the ADDIE model, but focused solely on the design and validation stages. The subjects were 20 elementary school teacher education (PGSD) students at Syiah Kuala University. Data were collected through model validation sheets and learning tools assessed by six experts. Validity testing using the Aiken's V method showed that the PBU-L model and Semester Learning Plan (RPS) had high validity, with an average coefficient of 0.89. These results demonstrate that the PBU-L model is feasible for implementation. Overall, this model is designed to support active, collaborative, and contextual learning, highly relevant for enhancing critical thinking skills in the digital age.